2014
DOI: 10.5198/jtlu.v7i3.439
|View full text |Cite
|
Sign up to set email alerts
|

Residential self-selection in travel behavior: Towards an integration into mobility biographies

Abstract: Abstract:The debate on residential self-selection (RSS) in the travel field seeks to answer the question of whether and to what extent spatial differences in traveling may be explained in spatial terms or to what extent, rather, they are explained by the unequal spatial distribution of people's social and personal characteristics, particularly their neighborhood and travel preferences. Arguing primarily from a European-specifically, German-perspective, this paper makes a case for integrating the RSS-travel lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 42 publications
2
20
0
1
Order By: Relevance
“…In this case, the BE-based policies would become ineffective or irrelevant to the promotion of transit use or biking and walking. The concern of RSS generated a new wave of studies reexamining the BE–travel connection (e.g., Cao, Mokhtarian, and Handy 2009a, 2009b; Handy, Cao, and Mokhtarian 2006; Kamruzzaman et al 2015; Mokhtarian and Cao 2008; Næss 2012; Scheiner 2014; TRB and IMNA 2005; Zhou and Kockelman 2008). Though most of these studies reconfirmed the effects of BE on travel after the self-selection bias is corrected, they reported shrinking magnitudes of BE effects when travelers’ preferences and attitudes are considered.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the BE-based policies would become ineffective or irrelevant to the promotion of transit use or biking and walking. The concern of RSS generated a new wave of studies reexamining the BE–travel connection (e.g., Cao, Mokhtarian, and Handy 2009a, 2009b; Handy, Cao, and Mokhtarian 2006; Kamruzzaman et al 2015; Mokhtarian and Cao 2008; Næss 2012; Scheiner 2014; TRB and IMNA 2005; Zhou and Kockelman 2008). Though most of these studies reconfirmed the effects of BE on travel after the self-selection bias is corrected, they reported shrinking magnitudes of BE effects when travelers’ preferences and attitudes are considered.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is partly in confirmation with the results of a few studies emerging from the high-income countries. Many of the studies though report on a significant association between the availability of public transportation services and residential location choices (such as Heinen et al 2018;Scheiner 2014;Boone-Heinonen et al 2010;Cao et al 2009;Cao 2014;Naess 2009); only a few of them found a marginal association between attitudes towards travel Table 3 The results of the chi-square tests of location decision reasons in the sample modes and choices made for a residential location (Ettema and Nieuwenhuis 2017;de Vos et al 2012;Schwanen and Mokhtarian 2004), thus pointing out the insignificant effect of car ownership on the established relationship between the availability of public transportation and residential location choices. Different types of neighbourhood in Egypt can play a role in the self-selection process within the formal or the informal markets.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a very few studies on the topic emerging from the Middle East and North Africa (MENA) region, it is difficult to find similar studies offering insights for better conceptual understanding of the topic. The studies from the high-income countries mainly report on the factors determining the peoples' housing choices as proximity to social contacts and networks;, school quality (Guidon et al 2019);, mobility, travel attitude, and built environment (Zang et al 2019;Heinen et al 2018;Ettema and Nieuwenhuis 2017;Scheiner 2014;Boone-Heinonen et al 2010;Cao et al 2009;Cao 2014;Naess 2009);, accessibility to jobs and services (Baraklianos et al 2018;Hu and Wang 2019);, and affordability and neighbourhood quality, including school quality (Lee and Waddell 2010;Bayoh et al 2006). Generally, such studies reporting on the factors of housing location choices in the Middle East and North Africa (MENA) region are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Studies supply evidence that the built environment and previous experiences of mobility influence travel behaviour (see, e.g. Krizek , ; Cao et al ; Lanzendorf ; Scheiner for studies where the effects of self‐selection were not taken into account, and Cao et al that accounted for the effects). This idea is supported by the findings from Krizek (2000 in Cao and Mokhtarian , p. 74), who found that ‘more than a half of his sample moved to a neighbourhood whose environmental characteristics were similar to those of their previous neighbourhood, and that few changes in household travel behaviour after residential relocation were observed’.…”
Section: Introductionmentioning
confidence: 99%